An Introduction to Computer Networks - Dordal, Peter Lars (Open textbook library., 2020)
An Introduction to Computer Networksis a free and open general-purpose computer-networking textbook, complete with diagrams and exercises.It covers the LAN, internetworking and transport layers, focusing primarily on TCP/IP. Particular attention is paid to congestion; other special topics include queuing, real-time traffic, network management, security and the ns simulator. The book is suitable as the primary text for an undergraduate or introductory graduate course in computer networking, as a supplemental text for a wide variety of network-related courses, and as a reference work.